Computer Vision and Medical Image Processing: a brief survey of application areas - Párraga Álava, Jorge Antonio (2015)
Every day is greater the number of images obtained to characterize the anatomy and functions of the human body, because of this the automation of the medical image processing has become a practice to improve the diagnosis and treatment of certain diseases. In this study the main areas of application of computer vision to the digital processing of medical images are reviewed. It begins with the selection of the three edges with more publications available in Springer, ScienceDirect, Wiley, and IEEE which are: segmentation of organs and lesions, feature extraction in optical images and labelling machine on x-ray images. Over them, latest algorithms, techniques and methods for medical imaging processing are analyzed exposing its main characteristics and ways of use.